Desempenho e dispêndio metabólico-ventilatório nos testes clínicos funcionais e a influência de um programa de treinamento físico aeróbio em pacientes com doença pulmonar obstrutiva crônica - Marrara, Kamilla Tays (Universidade Federal de São Carlos, 2011)
Objectives: To compare the metabolic demand ( O2/ O2peak), ventilatory demand ( E/MVV), dyspnea, fatigue on lower limbs (LL), oxygen peripheral saturation (SpO2) and functional capacity (number of climbs in step and work efficiency) at the peak of the six minutes step test (ST6) among patients with chronic obstructive pulmonary disease (COPD) stages II and III; Verify that there is relation of number of climbs in step with the first second forced expiratory volume (FEV1), BODE index, SpO2 and oxygen consumption ( O2) peak obtained in TD6, as well as with the distance walked in the six minutes walk test (6MWT) and in incremental symptom-limited cardiopulmonary test (CPT). Methods: Were evaluated 19 patients with stage II of COPD (50%  forced expiratory volume in one second (FEV1) 80%), composing the Group 1 (G1) and 16 with stage III of COPD (30%  FEV1  50%), constituting the Group 2 (G2) through ST6, 6MWT and CPT. Results: Were observed values significantly greater than dyspnea obtained at the peak of ST6 for G2, as well as significantly lower values of SpO2 at the peak of this test to the same group, as well as the number of climbs in step and distance walked in 6MWT and CPT. The number of climbs in step showed positive correlation with the SpO2 for G2, with r = 0.85. Conclusion: The patients with COPD stage III provided greater perception of dyspnea and desaturation in the ST6. In addition the same demonstrated reduced functional capacity when compared to patients with COPD stage II. And with relationship of number of climbs in ST6 with several variables, noted strong correlation with the SpO2 for patients with COPD stage III.
Keywords: Fisioterapia; Exercícios; Tolerância ao exercício; Teste de degrau; Atividades de vida diária; VNI (Ventilação Não Invasiva); Exercise; Exercise tolerance; Chronic obstructive pulmonary disease; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL